Cytological analysis of early microspore divisions leading to gametic embryo formation in Quercus suber L. anther cultures - Pintos, B; Manzanera, J A; Bueno, M A (Acta Physiologiae Plantarum, 2005)
The cor re la tion be tween the phenologic stage of the in flo res - cence and the microspore de vel op ment stage was stud ied. Cyto log i cal ex am i na tions of the de vel op ment of micro spores dur - ing in vi tro an ther cul ture of cork oak (Quercus suber L.), were car ried out dur ing the first four weeks of cul ture. To ob serve the di vi sion oc cur ring in the micro spores, an thers were taken ran domly from the cultures after heat shock treatment and were stained with DAPI. Most of the an thers re spond ing to a heat stress treat ment con tained 91 % vacuolated micro spores, in di cat ing that this de vel op men tal stage is re spon sive to embryo genesis in duc tion in cork-oak micro spores. Af ter the heat shock treat ment some cork-oak micro spores were in duced and ini ti ated the embryogenic path way with the oc cur rence of nu mer ous sym met ric mi to sis, pro duc ing struc tures with two to ten or more nu clei. These lead to the for ma tion of high num - bers of multicellular cork-oak micro spores (pro-em bryos). Twenty-forty days af ter in duc tion, small white glob u lar and cotyledonal em bryos were ob served, which fur ther de vel oped root and shoot, re gen er at ing plantlets.
Keywords: anther culture; Cork oak; microspore embryogenesis; Quercus suber

Cytological analysis of early microspore divisions leading to gametic embryo formation in Quercus suber L. anther cultures - Pintos, B.; Manzanera, J. A.; Bueno, M. A. (Acta Physiologiae Plantarum, 2005)
The cor re la tion be tween the phenologic stage of the in flo res - cence and the microspore de vel op ment stage was stud ied. Cyto log i cal ex am i na tions of the de vel op ment of micro spores dur - ing in vi tro an ther cul ture of cork oak (Quercus suber L.), were car ried out dur ing the first four weeks of cul ture. To ob serve the di vi sion oc cur ring in the micro spores, an thers were taken ran domly from the cultures after heat shock treatment and were stained with DAPI. Most of the an thers re spond ing to a heat stress treat ment con tained 91 % vacuolated micro spores, in di cat ing that this de vel op men tal stage is re spon sive to embryo genesis in duc tion in cork-oak micro spores. Af ter the heat shock treat ment some cork-oak micro spores were in duced and ini ti ated the embryogenic path way with the oc cur rence of nu mer ous sym met ric mi to sis, pro duc ing struc tures with two to ten or more nu clei. These lead to the for ma tion of high num - bers of multicellular cork-oak micro spores (pro-em bryos). Twenty-forty days af ter in duc tion, small white glob u lar and cotyledonal em bryos were ob served, which fur ther de vel oped root and shoot, re gen er at ing plantlets.
Keywords: anther culture; Cork oak; microspore embryogenesis; Quercus suber

Embriogénesis gamética para obtención de haploides en alcornoque. - Bueno, A.; GÓMEZ, A.; Boscaiu, M.; Manzanera, J. A.; Vicente, O. (II Congreso Forestal Español, 1997)
Inducción of haploid embryos and regeneration of plantlets have been obtained for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by culture at 25°C in a simple agar medium without growth regulator.s. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytic development of the microspores and for the induction of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that like most forest trees, are still recalcitrant in anther culture.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: anther culture; Cork oak; Haploid plants; Stress

Embriogénesis gamética para obtención de haploides en alcornoque. - Bueno, A; GÓMEZ, A; Boscaiu, M; Manzanera, J A; Vicente, O (II Congreso Forestal Español, 1997)
Inducción of haploid embryos and regeneration of plantlets have been obtained for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by culture at 25°C in a simple agar medium without growth regulator.s. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytic development of the microspores and for the induction of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that like most forest trees, are still recalcitrant in anther culture.
Keywords: anther culture; Cork oak; Haploid plants; Stress

Stress-induced formation of haploid plants through anther culture in cork oak (Quercus suber) - Bueno, Maria Angeles; Gomez, Arancha; Boscaiu, Monica; Manzanera, Jose Antonio; Vicente, Oscar (Physiologia Plantarum, 1997)
Induetion of haploid embryos and regeneration of plantlets have been obtained, for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by eulture at 25°C in a simple agar medium without growth regulators. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of' several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytie development of the mierospores and for the induetion of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that, like most forest trees, are still recalcitrant in anther culture.
Keywords: anther culture; Cork oak; flow cytometry; Haploid plants; heat shock; Quercus suber; starvation; Stress

Stress-induced formation of haploid plants through anther culture in cork oak (Quercus suber) - Bueno, Maria Angeles; Gomez, Arancha; Boscaiu, Monica; Manzanera, Jose Antonio; Vicente, Oscar (Physiologia Plantarum, 1997)
Induetion of haploid embryos and regeneration of plantlets have been obtained, for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by eulture at 25°C in a simple agar medium without growth regulators. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of' several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytie development of the mierospores and for the induetion of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that, like most forest trees, are still recalcitrant in anther culture.
Keywords: anther culture; Cork oak; flow cytometry; Haploid plants; heat shock; Quercus suber; starvation; Stress